PELATIHAN PEMBUATAN DAN PEMASARAN ZPT ALAMI DI KELURAHAN CAWANG BARU KECAMATAN SELUPU REJANG - Ria Dwi Jayati; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2021)
The Community Partnership Program that we propose is expected to help the Cawang Baru Village community in general and the Adelia IRT group in particular in the manufacture and marketing of natural Growth Stimulating Substances (PGR). Cawang Baru Village located in Selupu Rejang District is an agricultural area that produces many types of agricultural crop commodities. Besides these facts, there is also a lot of people who love flowers, especially mothers. So far, farmers and ornamental plant hobbyists in Cawang Village are new to cultivating or multiplying plants in addition to using fertilizers but also using PGR sold in the market, the price of manufactured PGR in the market is quite expensive and a little difficult to find in conventional agricultural shops because of its low content naturally can have a negative effect on the environment. Considering the costs involved in buying chemical PGR and its negative impact on the environment, making your own PGR by utilizing natural materials that are around is the right solution to deal with the problem of costs and environmental impacts. To achieve this goal, we used the method of observation, socialization, training and continued with direct practice. The long-term goal of this activity is to create business opportunities for the PKK Adelia group by utilizing natural materials as PGR whose existence is needed by farmers and ornamental plant hobbyists. The output targets of the activity are (1) increasing partners' knowledge, skills and income, (2) producing natural PGR products. Publication output target: service results published in community service journals.